Music and speech prosody: a common rhythm - Hausen, Maija; Torppa, Ritva; Salmela, Viljami R.; Vainio, Martti; Särkämö, Teppo (Frontiers in Psychology, 2013)
Disorders of music and speech perception, known as amusia and aphasia, have traditionally been regarded as dissociated deficits based on studies of brain damaged patients. This has been taken as evidence that music and speech are perceived by largely separate and independent networks in the brain. However, recent studies of congenital amusia have broadened this view by showing that the deficit is associated with problems in perceiving speech prosody, especially intonation and emotional prosody. In the present study the association between the perception of music and speech prosody was investigated with healthy Finnish adults (n = 61) using an on-line music perception test including the Scale subtest of Montreal Battery of Evaluation of Amusia (MBEA) and Off-Beat and Out-of-key tasks as well as a prosodic verbal task that measures the perception of word stress. Regression analyses showed that there was a clear association between prosody perception and music perception, especially in the domain of rhythm perception. This association was evident after controlling for music education, age, pitch perception, visuospatial perception and working memory. Pitch perception was significantly associated with music perception but not with prosody perception. The association between music perception and visuospatial perception (measured using analogous tasks) was less clear. Overall, the pattern of results indicates that there is a robust link between music and speech perception and that this link can be mediated by rhythmic cues (time and stress).